The Impact of Work Stress on The Quality of Work Life By Applying to Qatar National Bank (QNB) - Mustafa, Amal Mohamed (The Arab Journal of Administration, 2024)
This study aims to identify the impact of work stress on the quality of work life, as finding the reasons that increase work stress and trying to reduce its negative effects will positively affect the quality of work life, which supports increasing employee satisfaction, loyalty, and belonging to the organization, and then increasing its productivity and profitability. There is no doubt that this will in turn be reflected in creating balance and harmony between the professional and personal lives of employees. This study was applied to employees of one of the branches of Qatar National Al Ahli Bank. The study was based on the descriptive analytical approach. The questionnaire was conducted on a sample of employees of the bank in the target community. The researcher relied on random sampling and (150) responses out of 400 were collected. The study found that there is a significant relationship between the dimensions of work stress represented by (organizational structure- organizational leadership style- wages and rewards- workload) on the quality of work life represented by (functional and organizational aspects- the physical and moral work environment), where the statistical analysis proved the validity of the hypothesis. President: There is an inverse relationship between work pressures and the quality of work life. The first sub-hypothesis was also proven to be valid, with the presence of an inverse relationship between the organizational structure and the quality of work life. The second sub-hypothesis was also proven to be valid, with the presence of a direct relationship between organizational leadership style and the quality of work life. The third sub-hypothesis was also proven to be valid. There is a direct relationship between wages, rewards, and quality of work life. However, the fourth sub-hypothesis regarding the workload dimension was rejected. The study proved that there is an insignificant effect of the workload variable on the quality of work life. Then the researcher concluded this study with a number of recommendations, the most important of which were: the need to establish an effective mechanism to alleviate and address work pressures in the banking sector, and that the ethical charter and organizational culture of the institution take into account the distribution of work to employees in a way that is proportionate to their abilities and potentials without draining their efforts and energies so that they achieve a quality of work life. Ensuring equality and justice among employees in various matters and their participation in the decision-making process, and the necessity of following administrative policies that reduce work pressures, such as policies (job enrichment- job expansion- and employee empowerment).